Characterization of membrane protein interactions by peptidisc-mediated mass photometry - John William Young; Emanuel Pfitzner; Raman van Wee; Carla Kirschbaum; Philipp Kukura; Carol V. Robinson (iScience, 2024)
Summary: Membrane proteins perform numerous critical functions in the cell, making many of them primary drug targets. However, their preference for a lipid environment makes them challenging to study using established solution-based methods. Here, we show that peptidiscs, a recently developed membrane mimetic, provide an ideal platform to study membrane proteins and their interactions with mass photometry (MP) in detergent-free conditions. The mass resolution for membrane protein complexes is similar to that achievable with soluble proteins owing to the low carrier heterogeneity. Using the ABC transporter BtuCD, we show that MP can quantify interactions between peptidisc-reconstituted membrane protein receptors and their soluble protein binding partners. Using the BAM complex, we further show that MP reveals interactions between a membrane protein receptor and a bactericidal antibody. Our results highlight the utility of peptidiscs for membrane protein characterization in detergent-free solution and provide a rapid and powerful platform for quantifying membrane protein interactions.